Mapping the O-Mannose glycoproteome in saccharomyces cerevisiae - Neubert, Patrick; Zatorska, Ewa; Loibl, Martin; Castells Ballester, Joan; Strahl, Sabine (Molecular & cellular proteomics, 2016)
O-Mannosylation is a vital protein modification conserved from fungi to humans. Yeast is a perfect model to study this post-translational modification, because in contrast to mammals O-mannosylation is the only type of O-glycosylation. In an essential step toward the full understanding of protein O-mannosylation we mapped the O-mannose glycoproteome in baker's yeast. Taking advantage of an O-glycan elongation deficient yeast strain to simplify sample complexity, we identified over 500 O-glycoproteins from all subcellular compartments for which over 2300 O-mannosylation sites were mapped by electron-transfer dissociation (ETD)-based MS/MS. In this study, we focus on the 293 O-glycoproteins (over 1900 glycosylation sites identified by ETD-MS/MS) that enter the secretory pathway and are targets of ER-localized protein O-mannosyltransferases. We find that O-mannosylation is not only a prominent modification of cell wall and plasma membrane proteins, but also of a large number of proteins from the secretory pathway with crucial functions in protein glycosylation, folding, quality control, and trafficking. The analysis of glycosylation sites revealed that O-mannosylation is favored in unstructured regions and β-strands. Furthermore, O-mannosylation is impeded in the proximity of N-glycosylation sites suggesting the interplay of these types of post-translational modifications. The detailed knowledge of the target proteins and their O-mannosylation sites opens for discovery of new roles of this essential modification in eukaryotes, and for a first glance on the evolution of different types of O-glycosylation from yeast to mammals.
Gesehen am 19.06.2017